Pregnancy diagnosis in Black Bengal goat by progesterone assay (Bangladesh Journal of Animal Science, 2014)
Pregnancy is the main event in the life of a female mammal to reproduce the progeny and maintain the descents of the species. Progesterone level in the plasma is one of the indications of stages of pregnancy of an individual and the present study was undertaken to determine the progesterone level in different stages of pregnant Black Bengal does and to correlate blood progesterone level with stages of pregnancy in Black Bengal does. For this experiment the blood samples were collected from different stages of pregnant and non-pregnant Black Bengal does, kids and bucks, and subjected to use for further study.  The progesterone level was measured at 3 different stages of pregnancy (25-30 days, 60- 70 days, and 90-92 days) using the test kit (EIA TEST KIT Progesterone, Biocheck, Inc. Foster city, CA 94404 USA). Progesterone was also assayed in different ages of non-pregnant does, kids and bucks blood as the control. The logarithmic graph paper was used to calculate the progesterone level.  The progesterone levels were found 1.5 ng/ml, 6.6-9.3 ng/ml and 14-15.5 ng/ml in 25-30 days, 60-70 days and 90-92 days of pregnancy, respectively.  In case of non-pregnant does the progesterone level varied from 0.19-6.6 ng/ml in different ages.  Whereas the progesterone level was found between